PENGARUH KUALITAS AUDIT, KEPEMILIKAN INSTITUSIONAL, DAN INVESTASI JANGKA PANJANG TERHADAP FUTURE EARNINGS RESPONSE COEFFICIENT (FERC) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Williem Williem; Titik Aryati (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2017)
The objective of this research was to examine the effect of audit quality, institutional ownership, and long-term investment to the future earnings response coefficient (FERC) on companies listed in the Indonesia Stock Exchange. The research data was obtained from annual reports and financial sites Indonesian Stock Exchange (BEI). Total samples used in this research as many as 126 samples. This research uses multiple regression analysis. The results of this study indicate that (1) audit quality positive influence on FERC, (2) institutional ownership does not influence on FERC, (3) long-term investments negatively influence on FERC.